Trends in Safety Culture Research: A Scopus Analysis - Al-Baraa Abdulrahman Al-Mekhlafi; Noreen Kanwal; Mohammed Nasser Alhajj; Ahmad Shahrul Nizam Isha; Abdullah O. Baarimah (MDPI, 2025)
Indexed by Scopus/ERA